Management of orbital conjunctival epithelial inclusion cyst using trichloroacetic acid (20%) in an outpatient setting. (3rd March 2020) - Gallagher, David; Power, Barry; Hughes, Emily; Fulcher, Tim
ABSTRACT: Conjunctival epithelial inclusion cysts are an infrequent complication in anophthalmic sockets. The ocular prosthesis may become difficult to retain or it may cause local discomfort. Treatment options described include surgical resection, marsupialisation, and the use of injected sclerosing agents. We present a case of a 27-year-old female who developed a conjunctival epithelial inclusion cyst two years after a left eye evisceration. This invariably caused the ocular prosthesis to become cosmetically unacceptable. Trichloroacetic acid 20% (TCA) was injected intracystically as a minor procedure at the slit lamp. Four months later there was no recurrence of the cyst and the prosthesis retained an excellent position in the socket. This case highlights the successful treatment of a conjunctival epithelial inclusion cyst with TCA (20%) without the need for a surgical procedure.